Small Steps to the Big Picture for Health-Promoting Applications Through the Use of Chickweed (Stellaria media): In Vitro, In Silico, and Pharmacological Network Approaches - ŞENKARDEŞ, İSMAİL (My University, 2024)
Stellaria media L., also called chickweed, is widespread in all parts of the world. In the present study, we investigated the biological properties and chemical profiles of different extracts (ethyl acetate, ethanol, ethanol/water, and water) of S. media. The chemical profiles were examined using UHPLC/MS/MS technique. Regarding the biological properties, antioxidant properties as well as enzyme-inhibiting and cytotoxic effects of the extracts were demonstrated by in vitro methods. To obtain further information about the structure-ability relationship, network pharmacology and molecular docking were also performed. Twelve phenolic compounds were identified in the extracts and most of them were flavonoids (apigenin, kaempferol derivatives, etc.). The water extract showed the best free radical scavenging activity, while the ethanol was the most active in reducing power tests. When inhibiting AChE, the ethyl acetate extract showed the best inhibitory effect. The water extract has a good cytotoxic effect on HepG2 (cell viability: 33.9% at a concentration of 100 g/mL). The analysis, performed using the STRING database, included these 45 cancer-associated targets. The identified hub genes were TP53, CDKN2A, PTEN, KRAS, and HRAS. In molecular docking analysis, acacetin-O-hexoside-O-deoxyhexoside and napigenin-7-O-hexoside exhibit remarkable binding energies with proteins. Consequently, S. media can be potential raw materials for designing functional formulations in the pharmaceutical, nutraceutical, and cosmeceutical industries.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; Tarım Ve Çevre Bilimleri (Age); Tarım Bilimleri; Gıda Bilimi Ve Teknolojisi; Agriculture & Environment Sciences (Age); Food Science & Technology; Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences; antioxidant; health-promoting; HepG2; Stellaria media